Investigation of model parameter variation for tension control of a multi motor wire winding system - Chong, Shin Horng; Subari, Hanafi; Hee, Wai Keat; Chong, Wen Yee; Md Nawawi, Mohamad Riduwan; Othman, Md Nazri (2015)
Tension is the force required to pull the wire against the accumulation of all resistance, forces and loads. Tension is one of the important controlled parameters in winding process in order to determine the quality of the product. Winding process in electric discharge machine (EDM) wire manufacturing is the last process before the product is packed and sent to customers. In EDM wire manufacturing process, incorrect tension will result in wire winding failure and wire straightness failure. Since it is the last process in EDM wire manufacturing, it is needed to ensure that there is no reject product contributed in this process. The increase of the pendulum dancer fluctuation and deviation angle when the winding diameter gets bigger especially when it is in high speed will course winding tension problem. This project mainly describes about the modelling of the system and the variation parameters that affects the system performance. The system performance is validated by changing the value of radius of winder.